Impact of Combined Grazing by Prairie Dogs with Goats or Cattle on Vegetation and Hydrology of a Chihuahuan Desert Grassland - Mellado, M; Olvera, A; Duenez, J; Mellado, J (Annals of Arid Zone, 2016)
Impact of combined grazing by prame dogs with goats or cattle on vegetation and hydrology of a Chihuahuan desert grassland of northern Mexico was assessed. Twice replicated grazing treatments were: (1) yearlong continuous goat grazing at a high intensity in a prairie dog colony, and (2) sequential rotation grazing by cattle along with prairie dogs at a moderate intensity. The pasture grazed by prairie dogs with cattle supported fewer plant species (n = 50) than the pasture grazed by goats with prairie dogs (n = 63). The synergistic grazing by goats and prairie dogs caused a 68% reduction in the aboveground biomass, with a directional change favoring herbaceous vegetation at the expense of grasses. The average biomass production of forbs increased 65% and the average grass standing crop decreased by 400% under the combined grazing regime of prairie dogs and goats, in comparison to the pasture grazed by prairie dogs and cattle. Most forbs with higher contribution to the total standing crop on the site grazed by prairie dogs and goats were non-edible. The standing crop of shrubs was higher (P<0.05) on the site grazed by prairie dogs and goats than the site grazed by prairie dog and cattle.Â· Plant diversity was higher on the pasture grazed by prairie dogs and goats than the pasture grazed by prairie dogs and cattle. The infiltration rate was higher (P<0.05) in the pasture grazed by prairie dogs and cattle than the pasture grazed by prairie dogs and goats. Uncontrolled continuous grazing by goats at a heavy stocking rate in a prairie dog colony had a drastic impact on plant community structure and hydrology in the vicinity of the goat pens in comparison to the site grazed by prairie dogs and cattle. Thus, confinement of large herds of goats to the same pasture year-round in prairie dog colonies must be avoided.